2019
DOI: 10.12659/ajcr.912115
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Stage IV Chromophobe Renal Cell Carcinoma Treated with the Oncolytic ECHO-7 Virus, Rigvir®

Abstract: Patient: Male, 59Final Diagnosis: Chromophobe renal cell carcinoma, stage IVSymptoms: Discomfort in the right hypochondriumMedication: Oncolytic virus RigvirClinical Procedure: Nephro-adrenalectomySpecialty: OncologyObjective:Unusual or unexpected effect of treatmentBackground:Renal cell carcinoma is the most commonly diagnosed primary malignant tumor of the kidney in adults, and includes the variant of chromophobe renal cell carcinoma. Despite new targeted therapies that improve progression-free survival (PFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Chemotherapy regimen and targeted therapies showed little activity in SRCC [16]. Renal cell cancer has previously been reported to show sensitivity to immunotherapy, indicating the possible advantage of immunomodulating therapies over standard treatment [17]. Prospective trials assessing new drugs, including immune checkpoint inhibitors, are currently ongoing study on improved SRCC survival [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy regimen and targeted therapies showed little activity in SRCC [16]. Renal cell cancer has previously been reported to show sensitivity to immunotherapy, indicating the possible advantage of immunomodulating therapies over standard treatment [17]. Prospective trials assessing new drugs, including immune checkpoint inhibitors, are currently ongoing study on improved SRCC survival [16].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell cancer has previously been reported to show sensitivity to immunotherapy, indicating the possible advantage of immunomodulating therapies over standard treatment [17].…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up CT imaging for more than one year, showed no disease progression, cancer metastasis, or lymph node involvement. Despite the estimated OS for patients with RCC stage 4, which equals less than 26 months, the patient survived over 33.7 months (remaining alive at the time of the report) and he never received any medical treatment except Rigvir [100].…”
Section: Urological Cancersmentioning
confidence: 92%
“…Another research showed similar results in evaluating the effect of Rigivir on small cell lung cancer and histiocytic sarcoma [ 199 ]. In 2015, Zaurbek et al [ 200 ] described a clinical case of advanced renal cell cancer that responded well to Rigvir treatment: tumor metastases are stabilized three months after the treatment. These promising results have reinforced the opinion that Rigvir could significantly prolong survival in patients without serious side effects and it could be recommended in long-term treatment.…”
Section: Viral Families Most Used In Virotherapymentioning
confidence: 99%